Clinical Study of Godhuma Yusha (Triticum Aestivum Linn.) in Amlapitta (Gastritis) - S Roja Bai,; Renu Dixit,; K.V.Vijaya Bhaskara Reddy,; Rajiv Dixit, (International Journal of Ayurveda and Pharma Research, 2024)
Gastritis is a condition that results from inflammation of the gastric mucosal layer characterized by swelling, pain and mucosal membrane irritation of the stomach. Gastritis in Ayurveda can be compared to Amlapitta and consumption of Godhuma in Ayurvedic classics is shown to be very effective. Objectives: To evaluate the study on Godhuma yusha in Amlapitta (gastritis) and assess its effects on Amlapitta (gastritis) Study Design: This was a randomized controlled study with 30 patients divided into two groups. Group A and Group B. Intervention: Group A included 15 patients and was administered 15ml of Godhuma yusha twice daily for a period of 3months. Group B also had 15 patients and was administered placebo 5gm twice daily. All the patients were followed at an interval of 15 days up to 3 months. Results: All the parameters such as Amlodgara, Hritkantadaha, Gourava, Utklesha, Avipaka and Agnimandya showed significant results in both the groups; Group A and Group B after the treatment compared to before treatment with p<0.0001 with more significant results in Group A compared to Group B with statistically significant results (p<0.001). Conclusion: Godhuma Yusha consumption was more effective compared to placebo in the management of Amlapitta.